2016
DOI: 10.1149/2.0461702jes
|View full text |Cite
|
Sign up to set email alerts
|

Local Corrosion Behavior of Additive Manufactured AlSiMg Alloy Assessed by SEM and SKPFM

Abstract: The local corrosion behavior of additive manufactured AlSiMg specimens was studied using the SEM and SKPFM techniques. A morphological characterization of corroded areas revealed that crystallographic pitting developed in the aluminium grains inside the melt pool borders, from where corrosion spread to adjacent zones. The local Volta potential analysis showed that there is a close relation between the cellular grain size and the potential difference between the silicon and the aluminium phase. SKPFM measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 23 publications
29
123
0
Order By: Relevance
“…The SLM AlSi10Mg specimens presented an apparently better corrosion resistance than their cast counterparts (albeit only through evaluation by corrosion potential values, which are not a measure of corrosion rate). If the results are to be considered reliable, then they may be in agreement with Leon, et al, 89 though they contradict the results obtained by Revilla, et al 88 In contrast, Fathi, et al, 91 suggested that grinding the SLM AlSi10Mg specimens was detrimental to the continuous oxide layer formed on the AP specimen surface, inconsistent with the findings of Leon, et al 90 Therefore, the role of surface finish (i.e., roughness) on the corrosion of SLM AlSi10Mg remains unclear. This lack of clarity is exacerbated by a lack of standardized testing by many authors, and also by the use of an arguably aggressive electrolyte for such an alloy, which might obscure surface finish effects.…”
Section: Al Alloysmentioning
confidence: 55%
See 3 more Smart Citations
“…The SLM AlSi10Mg specimens presented an apparently better corrosion resistance than their cast counterparts (albeit only through evaluation by corrosion potential values, which are not a measure of corrosion rate). If the results are to be considered reliable, then they may be in agreement with Leon, et al, 89 though they contradict the results obtained by Revilla, et al 88 In contrast, Fathi, et al, 91 suggested that grinding the SLM AlSi10Mg specimens was detrimental to the continuous oxide layer formed on the AP specimen surface, inconsistent with the findings of Leon, et al 90 Therefore, the role of surface finish (i.e., roughness) on the corrosion of SLM AlSi10Mg remains unclear. This lack of clarity is exacerbated by a lack of standardized testing by many authors, and also by the use of an arguably aggressive electrolyte for such an alloy, which might obscure surface finish effects.…”
Section: Al Alloysmentioning
confidence: 55%
“…The effect of the use of recycled powder, laser scan passes, and layer thickness on the corrosion of the AlSi10Mg produced by SLM was studied by Revilla, et al 88 In the study, the corrosion potential (E corr ) values derived from potentiodynamic polarization of the cast and SLM AlSi10Mg specimens were similar, with values ranging between −0.7 V Ag/AgCl and −0.6 V Ag/AgCl (Figure 4). The corrosion characteristics observed for SLM and cast AlSi10Mg were correlated by Revilla, et al, who observed similar microstructure and composition.…”
Section: Al Alloysmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, the presence of silicon inside the oversaturated α‐Al phase increases its electrochemical potential. Revilla et al measured the Volta potential differences between Al and Si inside and outside the melt pool borders of specimen without heat treatment. The authors concluded that such difference is much higher inside the melt pool border than outside.…”
Section: Resultsmentioning
confidence: 99%